Analisis Performa Mata Uang Virtual (Cryptocurrency) Menggunakan Preference Ranking Organization Method For Enrichment Evaluation (Promethee) - Farida, Yuniar; Khasanah, Zhara Shafira Uswatun (Rekayasa, 2021)
Cryptocurrencies are among the inventions that have caused a stir in the economy of late. Because in its use there are still pros and cons of various countries. Some countries reject the use of cryptocurrencies and others support the use of cryptocurrencies because it is considered a modernization of payment tools. Besides being used for payment instruments, cryptocurrencies can also be one of the options to invest. The number of cryptocurrencies that exist causes investors to be observant in making the right choices. In this study, the Promethee method was used I and II to determine the rank of 7 virtual currencies. Promethee I is a partial assessment method while Promethee II is a complete assessment method. The data used for ranking is obtained from the questionnaire "sentiment on the performance of cryptocurrencies". The results of the cryptocurrency performance analysis showed that the investment commodity of the most recommended in a row is Bitcoin with a net flow value of 0.33267, Cardano 0.14267, Ethereum 0.04800, Ripple 0.04733, Stellar -0.04733, Litecoin -0.04767 and Dogecoin -0.47567.